In Vitro Glutathione Supplementation Enhances Interleukin-2 Production and Mitogenic Response of Peripheral Blood Mononuclear Cells from Young and Old Subjects - Wu, Dayong; Meydani, Simin N; Sastre, Juan; Hayek, Michael; Meydani, Mohsen (The Journal of nutrition, 1994)
The effect of in vitro glutathione (GSH) supplementation on mitogenic response, interleukin-1, interleukin-2 and prostaglandin E2 production, and cellular GSH level in peripheral blood mononuclear cells (PBMC) from healthy young and old human subjects was studied. In vitro addition of GSH increased cellular GSH level (P < 0.001). Glutathione supplementation at concentrations between 2 to 10 mmol/L enhanced lymphocyte proliferation but at low concentrations (0.5 and 1 mmol/L) decreased mitogenic response. Glutathione-induced enhancement of lymphocyte proliferation due to phytohemagglutinin or concanavalin A was greater in the PBMC from old subjects than in those from young subjects. At optimal concentration (5 mmol), GSH increased interleukin-2 production (P < 0.05) and decreased prostaglandin E2 and leukotriene B4 production (P < 0.01) in both age groups. Furthermore, decreased PBMC mitogenic response by in vitro addition of prostaglandin E2 was reversed by GSH supplementation. Glutathione did not have an effect on interleukin-1 production by PBMC from young subjects; however, GSH supplementation tended (P = 0.08) to increase interleukin-1 production by PBMC from old subjects. We conclude that GSH supplementation enhances T cell-mediated mitogenic response in young and old subjects. This effect is due at least in part to decreased eicosanoid production.